Hermeneutics of Hadith on Multiplying Descendants: A Perspective of Hans George Gadamer - Kholily, Aaviy Lailaa (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2018)
The reproduce generation Hadist textually contains orders to have many offspring, butcan that Hadist still be applied to the contemporary context in order for exploding population causing many problems such as a quality of education, health, employment, public orderetc. This ultimately prompted the government to make family planning programs to anticipate the rate of population growth. The goverment claimed the the exploding population make the burden of the state will be more and more. In this study, researchers will attempt to study the reproduce generatuon Hadist depend on Gadamer hermeneutical perceptions, namely: First the reader or reviewer must be aware that the reader has its own horizon. Second, the readers have prejudice and hipotesa before reviewing, have assumptions as well. but the assumption must accept to be criticized and even modified according to the text content. Third, called the hermeneutic circle, which combines the horizon of the text with the horizon of the reader because certainly every text naturally has horizon when the text was born. Fourth, the application of the values ​​of the texts studied in the present context. The formulation of the issues raised in this study are: How the application of Gadamer's hermeneutical theory in understanding the Hadist. From this formulation of the problem the researchers found several things in between are: First, the message contained that hadith Rasulullah eager to have a lot of people on the Day of Judgment so that he will be proud of the number of Muslims. Secondly, we must still be applied in the present context because the goal is the number of Muslims in the future.